Children at risk of diabetes type 1. Treatment with acetyl-L-carnitine plus nicotinamide – Case reports - Fernandez, Ivana Cristina (2012)
Objectives: The aim was to evaluate the treatment with acetyl-L-carnitine (50 mg/kg/day) and nicotinamide (25 mg/kg/day) in children at risk of type 1 diabetes. This treatment was effective and harmless in experimental type 1 diabetes in mice. Patients: Nine out of seventy healthy participants of the type 1 diabetes risk study were treated. They were typified for diabetes with HLA-DQB1 and positive autoantibodies. Children with a first peak of insulin response ≤ 48 μU were randomly distributed in control and treated patients. Children evolution was followed with an intravenous glucose tolerance test. Control children were treated when was another risk parameter was added. During their evolution all children were treated. Results: Treatment periods differ (range: 120–16 months) because children began treatment at different times. During the treatment 4 patients recovered their parameters and the medication was suspended; 2 patients continued the treatment with favorable evolution. Two children evolved slowly with normal growth and development. One girl became diabetic because she was treated late. Conclusion: In children at risk, this treatment delays the development or remits the evolution of type 1 diabetes.